User Behavior in Social Networks Toward Privacy and Trust: Literature Review - Almogbel, Razan Saleh; Alkhalifah, Ali Abddulaziz (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Social networks (SNs) have become a significant part of daily life. It has become one of the most effective ways in which people communicate with each other. Huge amounts of data are generated and shared through SNS worldwide, where users share their personal and sensitive information. Therefore, disclosure of private information or identity and the loss of trust among users are among the most prominent and widespread privacy concerns. The main target of this study is to investigate the relationship between privacy, trust, and their effects on user behavior on Social networks. It provides a detailed and overall overview of the concepts and methods related to protecting the privacy and enhancing trust in Behavioral SNs users. In addition, it illustrates many of the key aspects of the research in the context of identity privacy and trust in users’ behavior on SNs and shows the most important restrictions and gaps that have been found and guidance on future research directions.